Hernán Pantoja: Una versión del mito de Inkarri en Amazonas - Rodríguez Villa, José (1987)
This paper presents the myth of Hernán Pantoja collected in the Andean area of ​​the Department of Amazonas and which presents in its content all the elements of the Inkarri myth whose main known versions have been collected in the southern and central part of the country. If Hernán Pantoja were a localized version of Inkarri, the framework for the dissemination of the myth would be extended much further north, which at least seemed to be limited to the northern area by the version of Vicos (Ancash) collected by Ortiz Rescaniere in 1965.